From bias to bliss: Racial preferences and worker productivity in tennis - Carsten Creutzburg; Wolfgang Maennig; Steffen Q. Mueller (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2024)
This study investigates the impact of differences in consumers racial preferences on worker productivity through the example of the home advantage (HA) effect using data on wins in mens professional tennis from 2001 to 2020 (pre-COVID-19). We identify players racial affiliation as one of five distinct race groups by combining clustering algorithms and facial recognition software. Our empirical design innovates by allowing us to distinguish among HA factors related to the presence of fans, referee bias, travel fatigue, and home-court familiarity. We provide evidence of social environments where Black players benefit more strongly from fan support than players of other races.
Keywords: J15; J71; L83; Z22; 330; Labor market discrimination; consumer discrimination; racial bias; productivity; home advantage